Polimorfismos de genes de interleucinas contribuem para a susceptibilidade genética na doença periodontal crônica - Manso, João Antonio Xavier (2020)
Chronic periodontal disease (CPD) is described as a recurrent inflammatory condition in the tooth supporting tissues, caused by bacterial infections and self-destructive processes of immune activity mediated by pro-inflammatory cytokines, of which the interleukins 1β, 6 and 8 that, together with other biomolecules, makes up the initial mechanisms of innate immunity. These molecules may have variations in their genes, such as single nucleotide polymorphisms (SNP), which together with environmental factors represent potential parameters in analyzes of susceptibility to the disease. The aim of this study was to investigate the involvement of polymorphisms of the IL1B, IL6 and CXCL8 genes, as well as sociodemographic and lifestyle aspects, with susceptibility to chronic periodontal disease in a group of volunteers from Goiânia city. Peripheral blood samples from 152 volunteers were obtained via venipuncture and grouped into controls and a case group (CPD), according to the result of the periogram, previously performed together with the questionnaire of habits and life style. The DNA of the samples was extracted through commercial kits and genotyped using the PCR-RFLP and qPCR techniques, according to the strategy adopted for the molecular marker used. The data were tabulated and submitted to the adequate statistical tests, all at 5% significance. A significant trend to develop CPD was detected for individuals who brush their teeth less than twice a day. The allele of minor frequency of the variants rs1143634, rs1800796, and rs2227539 were associated with CPD, revealing a significant predictive effect (p<0.05). Highlight for the T (rs1143634) and C (rs1800796) alleles, which were associated with increased risk, when inferred individually and together. Multifactorial aspects of disease have been confirmed, reporting the influence of genetic and environmental components on susceptibility, since minor frequency alleles of IL1B (rs1143634 T), IL6 (rs1800796 C), CXCL8 (rs2227539 A) genes and a low brus